Speaking Truth to Tyrannical Power: A Hadith Study on The Concept of The Best Jihad - Muhammad Zaini (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2026)
This research aims to examine the hadith that explains afdhal al-jihād kalimatu 'adlln 'inda shulthāni jāir (the best jihad is to convey justice in front of unjust leaders). In this study, the researcher focuses on the hadith narrated by Imam al-Turmuzi. The research was carried out on two things, namely in terms of the quality of the hadith and in terms of the lecture (explanation) of the intention contained in the mata. This type of research is a literature review (library research), by conducting a review of books and books related to the topic of discussion. The conclusion of this study; First, the hadith narrated by Imam al-Turmuzi regarding the issue studied is basically dha'if, because it is found that there are two narrators whose status is questionable, but because of the existence of supporting narrators who are tsiqah from other paths, this hadith is raised in quality from dha'if to hasan ligairihi, while the mata is saheeh. Second, the content of the hadith explains that justice must be delivered to the tyrannical leader, even though it is necessary to consider the risks experienced by people who commit jihad like this. Therefore, conveying the truth in front of the ruler is often dilemmatic if the one facing is the ruler who is feared. Abstrak Penelitian ini bertujuan untuk mengkaji hadits yang menjelaskan tentang afdhal al-jihād kalimatu ‘adlln ‘inda shulthāni jāir (jihad yang paling baik adalah menyampaikan keadilan di depan pemimpin yang zalim). Dalam kajian ini peneliti memfokuskan penelitian pada hadits yang diriwayatkan oleh Imam al-Turmuzi. Penelitian dilakukan pada dua hal, yaitu dari segi kualitas haditsnya dan dari segi syarahan (penjelasan) maksud yang dikandung matannya. Jenis penelitian ini adalah kajian pustaka (library risearch), dengan cara melakukan telaah terhadap kitab-kitab maupun buku yang berkaitan dengan tema pembahasan. Kesimpulan dari penelitian ini; Pertama, hadits yang diriwayatkan Imam al-Turmuzi terkait persoalan yang dikaji pada dasarnya adalah dha’if, karena ditemukan ada dua orang periwayat yang statusnya dipertanyakan, namun karena adanyanya periwayat pendukung yang tsiqah dari jalur lain maka hadits ini terangkat kualitasnya dari dha’if menjadi hasan ligairihi, sedangkan matannya shahih. Kedua, kandungan hadits tersebut menjelaskan bahwa keadilan itu mesti disampaikan kepada pemimpin yang zalim, meskipun demikian perlu untuk dipertimbangkan resiko yang dialami orang yang melakukan jihad seperti ini. Oleh karena itu, menyampaikan kebenaran di depan penguasa seringkali bersifat dilematis apabila yang dihadapi adalah penguasa yang ditakuti.